2016
DOI: 10.1002/jgm.2897
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of MMP‐2(‐735 C>T) and MMP‐9(‐1562 C>T) gene in risk of development of HAND and severity of HAND

Abstract: Individuals with the MMP-2 -735CT genotype, -735 T allele and combined genotype MMP-2 -735TT + MMP-9 -1562CC had an enhanced risk of developing HAND. Those with the MMP-2 -735 CT genotype, -735 T allele and combined genotype of MMP-2-735TT + MMP-9-1562CC were suggested to have protection from developing severe HAND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
4
2
Order By: Relevance
“…Furthermore, previous functional studies have reported a lower promoter activity as a consequence of the Sp1 binding site disruption, 51,76 predisposing to multiple diseases. 26,52,[77][78][79] In the present study, a lack of association with DN was obtained in Tunisians because the MAF distribution was comparable between the different comparison groups. Similarly, the À735C/T variant, which altered an Sp1 binding site and has previously been reported to alter MMP-2 gene transcription, 80 showed that the allelic transition C/T most likely does not influence the onset and progression of DN given the lack of allelic and genotypic association with DN.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Furthermore, previous functional studies have reported a lower promoter activity as a consequence of the Sp1 binding site disruption, 51,76 predisposing to multiple diseases. 26,52,[77][78][79] In the present study, a lack of association with DN was obtained in Tunisians because the MAF distribution was comparable between the different comparison groups. Similarly, the À735C/T variant, which altered an Sp1 binding site and has previously been reported to alter MMP-2 gene transcription, 80 showed that the allelic transition C/T most likely does not influence the onset and progression of DN given the lack of allelic and genotypic association with DN.…”
Section: Discussioncontrasting
confidence: 47%
“…The C/T transition at −1306 position in the promoter region of MMP‐2 gene results in the loss of Sp1 binding site, in reference to our in silico analysis results. Furthermore, previous functional studies have reported a lower promoter activity as a consequence of the Sp1 binding site disruption, 51,76 predisposing to multiple diseases 26,52,77–79 . In the present study, a lack of association with DN was obtained in Tunisians because the MAF distribution was comparable between the different comparison groups.…”
Section: Discussioncontrasting
confidence: 39%
“…Other MMP-3 alleles ( MMP-3-1612 5A allele and MMP-3-1612 5A/5A allele) presented a lower risk of HAND [ 128 ]. A polymorphism of the MMP-2 gene (MMP-2-735 C>T) has been implicated in risk of HAND development and severity, both alone and synergistically with a MMP-9 variation ( MMP-9-1562 C>T ) [ 129 ]. A SNP of the MMP-7 gene, resulting in MMP-7-181 A or G genotypes, was not associated with HAND, even though MMP-7 is upregulated by the Tat protein [ 130 ].…”
Section: Matrix Metalloproteinase (Mmp) Genesmentioning
confidence: 99%
“…Our study revealed no significant association of the MMP2 rs2285053 variant at position −735 (C>T) with AD risk and no effect on the age of AD onset and the degree of cognitive dysfunction monitored by the MoCA score. Regarding neurodegenerative disorders, only one study reported that individuals with the MMP2 −735CT genotype and −735T allele were at higher risk of developing HIV-associated neurocognitive disorders (HAND) [30]. As reported in other research studies, the −735C allele as a high producer was associated with MS risk in female patients [38], in patients with ischemic stroke in a Chinese population [39], and with breast cancer risk [40].…”
Section: Discussionmentioning
confidence: 85%
“…Genetic impact of MMP2 rs243866 (−1575 G>A) and rs2285053 (−735 C>T) polymorphisms on AD risk have not been analysed until now. However, one study presented a significant association of the rs2285053-T allele with susceptibility to develop HIV-associated neurocognitive disorders [30]. The first objective of the current investigation was to assess the association of MMP2 rs243866 (−1575 G>A) and rs2285053 (−735 C>T) polymorphisms with disease susceptibility in a group of Slovak patients with late-onset Alzheimer's disease by a case-control study.…”
Section: Introductionmentioning
confidence: 96%